The relationship between emotional appetite and bipolar features in obese and non-obese individuals - Budak, Ersin; Taymur, İbrahim; Önen, Sinay; Çaycı, Hacı Murat; Şenormancı, Güliz (The European Research Journal, 2019)
Objectives: It is known that many different positive and negative emotions can affect appetite and also, individuals who have bipolar features often have emotional fluctuations. In this study, it was aimed to investigate the relationship between emotional appetite and bipolar features in obese individuals.Methods: One hundred and ninety obese individuals who applied for bariatric surgery and 136 non-obese individuals were evaluated with Emotional Appetite Questionnaire (EMAQ), Beck- Depression Inventory (BDI), Beck-Anxiety Inventory (BAI) and The Temperament Evaluation of Memphis, Pisa, Paris and San-Diego Auto-questionnaire (TEMPS-A) in the study.Results: In obese individuals who applied for bariatric surgery, the frequency of bipolar disorder was found to be 2% and binge eating disorder (BED) frequency was 51.2%. It was found that scores of appetite in negative emotions were higher in obese individuals with BED compared to obese individuals and it was higher in obese individuals compared to normal weight individuals. Cyclothymic features explained 27.2%, 25.8% and 15.7% of scores of appetite in negative situations of obese individuals with BED, obese individuals without BED and normal weight individuals, respectively. Conclusions: As a result of this study, it can be concluded that scores of appetite in negative situations may be affected by cyclothymic features in obese individuals with BED, in obese and normal weight individuals. Depression and anxiety symptoms are effective factors in explaining scores of appetite in negative situations of obese individuals with BED, obese and normal weight individuals.